Intravenous Transplantation of Mesenchymal Stem Cells Reduces the Number of Infiltrated Ly6C+ Cells but Enhances the Proportions Positive for BDNF, TNF-1α, and IL-1β in the Infarct Cortices of dMCAO Rats - Yunqian Guan; Xiaobo Li; Wenxiu Yu; Zhaohui Liang; Min Huang; Renchao Zhao; Chunsong Zhao; Yao Liu; Haiqiang Zou; Yanli Hao; Zhiguo Chen (Stem Cells International)
The resident microglial and infiltrating cells from peripheral circulation are involved in the pathological processes of ischemia stroke and may be regulated by mesenchymal stem/stromal cell (MSC) transplantation. The present study is aimed at differentiating the neurotrophic and inflammatory roles played by microglial vs. infiltrating circulation-derived cells in the acute phase in rat ischemic brains and explore the influences of intravenously infused allogeneic MSCs. The ischemic brain injury was induced by distal middle cerebral artery occlusion (dMCAO) in SD rats, with or without MSC infusion in the same day following dMCAO. Circulation-derived infiltrating cells in the brain were identified by Ly6C, a majority of which were monocytes/macrophages. Without MSC transplantation, among the infiltrated Ly6C+ cells, some were positive for BDNF, IL-1β, or TNF-α. Following MSC infusion, the overall number of Ly6C+ infiltrated cells was reduced by 50%. In contrast, the proportions of infiltrated Ly6C+ cells coexpressing BDNF, IL-1β, or TNF-α were significantly enhanced. Interestingly, Ly6C+ cells in the infarct area could produce either neurotrophic factor BDNF or inflammatory cytokines (IL-1β or TNF-α), but not both. This suggests that the Ly6C+ cells may constitute heterogeneous populations which react differentially to the microenvironments in the infarct area. The changes in cellular composition in the infarct area may have contributed to the beneficial effect of MSC transplantation.